Strategic analysis of the external environment - Gogić Nemanja (Trendovi u Poslovanju)
The starting point from which we began our research was that many companies around the world could not predict and adapt to the new changes taking place in the environment (closure due to the corona virus pandemic, war in Ukraine, sanctions against Russia). Through strategic analysis, companies were able to gather information about planned scenarios and based on them, quality decisions could be made. The goal of the research is to point out the importance of strategic analysis, as an important phase in strategic planning, in order to avoid or mitigate all threats that have arisen in the external environment. The paper will present methods and techniques, with which management will collect data, all with the aim of making timely decisions. The methods we used for the work are: analysis and synthesis. The results of the research show us that if companies master these methods and techniques of strategic management on the one hand and have quality management on the other hand, they can largely predict the emergence of potential threats from the external environment. To avoid crisis situations, it is necessary for every company to incorporate crisis management within its organization.